Real Option Value over a Housing Market Cycle: West Berlin - John Clapp; Piet Eichholtz; Thies Lindenthal (European Regional Science Association (ERSA), 2012)
This paper analyzes how the dynamics of house prices are affected by the option to rebuild or enlarge existing dwellings. The curvature of option value and zoning limits provide identification of changes in option value over the cycle. For West Berlin homes with high development potential, our empirical results show that about 40 percent of the price increases during the "Big Bang" boom years (1989 through 1994) was related to increased option value. In the subsequent bust about 50 percent of their price decline was associated with decreased option value. For dwellings with low redevelopment potential 12 percent of the decline in real value can be attributed to changing option value.
Keywords: 330